Carfilzomib and dexamethasone maintenance following salvage ASCT in multiple myeloma: A randomised phase 2 trial by the Nordic Myeloma Study Group. (11th October 2021) - Gregersen, Henrik; Peceliunas, Valdas; Remes, Kari; Schjesvold, Fredrik; Abildgaard, Niels; Nahi, Hareth; Andersen, Niels Frost; Vangsted, Annette Juul; Klausen, Tobias Wirenfeldt; Helleberg, Carsten; Carlson, Kristina; Frølund, Ulf Christian; et al.
Abstract: Objective: We investigated the efficacy and safety of carfilzomib‐containing induction before salvage high‐dose melphalan with autologous stem‐cell transplantation (salvage ASCT) and maintenance with carfilzomib and dexamethasone after salvage ASCT in multiple myeloma. Methods: This randomised, open‐label, phase 2 trial included patients with first relapse of multiple myeloma after upfront ASCT who were re‐induced with four cycles of carfilzomib, cyclophosphamide and dexamethasone. Two months after salvage, ASCT patients were randomised to either observation or maintenance therapy with iv carfilzomib 27 → 56 mg/sqm and p.o. dexamethasone 20 mg every second week. The study enrolled 200 patients of which 168 were randomised to either maintenance with carfilzomib and dexamethasone (n = 82) or observation (n = 86). Results: Median time to progression (TTP) after randomisation was 25.1 months (22.5‐NR) in the carfilzomib‐dexamethasone maintenance group and 16.7 months (14.4–21.8) in the control group (HR 0.46, 95% CI 0.30–0.71; P = .0004). The most common adverse events during maintenance were thrombocytopenia, anaemia, hypertension, dyspnoea and bacterial infections. Conclusion: In summary, maintenance therapy with carfilzomib and dexamethasone after salvage ASCT prolonged TTP with 8 months. The maintenance treatment was in general well‐tolerated with manageable toxicity.